2013
DOI: 10.4238/2013.october.24.3
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Val66Met polymorphism and serum concentrations of BDNF with smoking in Thai males

Abstract: ABSTRACT. Many studies have suggested that brain-derived neurotrophic factor (BDNF) is involved in the reward system of addiction, and that nicotine may induce alterations in BDNF gene expression and its protein level within the mesocorticolimbic system. We investigated the BDNF levels and biochemical-hematological parameters of smoker and non-smoker groups, and examined the association of the Val66Met BDNF gene polymorphism with BDNF serum levels and cigarette smoking. The study sample comprised 311 Thai volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
1
19
1
Order By: Relevance
“…Consistently, multiple lines of evidence have documented that the genetic variant of rs6265 is significantly associated with various psychiatric diseases, including schizophrenia, bipolar, and eating disorders [53,54]. Furthermore, a number of genetic researches have reported a potential association between the common Val66Met variant and susceptibility to smoking-related phenotypes [23,[35][36][37][38][39][40][41][42]. For example, a large-scale GWAS [19] identified the polymorphism of rs6265 was significantly associated with smoking initiation (OR = 1.06, 95% CI 1.08-1.18, P = 3.6 × 10 −8 ).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Consistently, multiple lines of evidence have documented that the genetic variant of rs6265 is significantly associated with various psychiatric diseases, including schizophrenia, bipolar, and eating disorders [53,54]. Furthermore, a number of genetic researches have reported a potential association between the common Val66Met variant and susceptibility to smoking-related phenotypes [23,[35][36][37][38][39][40][41][42]. For example, a large-scale GWAS [19] identified the polymorphism of rs6265 was significantly associated with smoking initiation (OR = 1.06, 95% CI 1.08-1.18, P = 3.6 × 10 −8 ).…”
Section: Discussionmentioning
confidence: 86%
“…According to the "Quality of Reporting of meta-analysis and PRISMA guidelines" [43], nine studies [23,[35][36][37][38][39][40][41][42] were read carefully for potent eligible dataset according to a strictly systematic and comprehensive review (see Supplementary Fig. S1 for details).…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have provided strong evidence showing that exposure to nicotine leads to increased brain BDNF levels (Zhang et al, 2010;Suriyaprom et al, 2013;Jamal et al, 2015;Neves et al, 2017; for review, see Machaalani and Chen, 2018). The expression of BDNF and its tyrosine kinase receptor B receptor are linked to a7nAChRs where evidence shows BDNF and nAChRs mutually influencing each other (Freedman et al, 1993;.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, BDNF serum levels were lower in Met carriers than in Val/Val homozygotes [27, 28]. On the contrary, some studies found no association between this variant and BDNF serum levels [57, 58], while others found decreased BDNF serum levels in healthy Val/Val homozygotes when compared to Val/Met heterozygotes [59]. These inconsistent results across studies may be explained by a great variation in sample characteristics, assessment methods, and sample sizes.…”
Section: Discussionmentioning
confidence: 99%